2015
DOI: 10.18296/am.0002
|View full text |Cite
|
Sign up to set email alerts
|

Altered grades: A grey zone in the ethics of classroom assessment

Abstract: Students' grades are altered for a variety of reasons in educational systems worldwide. While there has been considerable research on teachers' grading practices, very little is known about the circumstances and reasons for grade alteration. This article closely examines eight instances where experienced teachers altered or were asked to alter students' grades in secondary schools in Ontario, Canada. Essentially, the teachers' responses were based on: a) the need for compassion; b) the desire to provide studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
7
0
7
Order By: Relevance
“…These controversies might arise from various sources (e.g., non-achievement factors) that teachers take into consideration as indicators of fairness of grades. For example, although very few studies have reported that teachers concur that grade decisions based on students' misbehavior and gender are unfair (Murillo & Hidalgo, 2017;Peterson, Childs, & Kennedy, 2004;Scott et al, 2014) other studies suggest that teachers consider factors such as effort, progress, compassion for students, desire to teach life lesson, and impact of grades on students' opportunities in their future lives as fair when deciding or adjusting grades (Alm & Colnerud, 2015;Green et al, 2007;Murillo & Hidalgo, 2017;Sambell, McDowell, & Brown, 1997;Scott et al, 2014;Tierney, 2015). However, the contribution of nonachievement related factors is regarded as unfair based on the concept of avoid score pollution.…”
Section: Avoid Score Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…These controversies might arise from various sources (e.g., non-achievement factors) that teachers take into consideration as indicators of fairness of grades. For example, although very few studies have reported that teachers concur that grade decisions based on students' misbehavior and gender are unfair (Murillo & Hidalgo, 2017;Peterson, Childs, & Kennedy, 2004;Scott et al, 2014) other studies suggest that teachers consider factors such as effort, progress, compassion for students, desire to teach life lesson, and impact of grades on students' opportunities in their future lives as fair when deciding or adjusting grades (Alm & Colnerud, 2015;Green et al, 2007;Murillo & Hidalgo, 2017;Sambell, McDowell, & Brown, 1997;Scott et al, 2014;Tierney, 2015). However, the contribution of nonachievement related factors is regarded as unfair based on the concept of avoid score pollution.…”
Section: Avoid Score Pollutionmentioning
confidence: 99%
“…In an era of assessment literacy, which includes fairness literacy as a significant dimension, teachers should be provided with a well-rounded body of knowledge of a multi-dimensional view of fairness in order to understand the interaction between general classroom fairness and assessment fairness. As an illustration, in spite of the principle of avoiding score pollution, teachers consider caring, future consequences of a grade for a student, effort, and desire to teach life lessons (Tierney, 2015) as fair factors in a grade alteration, which might be at odds with the current conception that only examines fairness within an assessment focus. Therefore, we argue that the CA fairness construct should be considered in relation to the elements of teaching, learning, and classroom interactions and reflective of themes from both assessment and non-assessment fairness domains within each of these elements.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…Most studies focus on teachers' practices, yet, teachers experience pressure from the principal, parents, and students when assigning grades. This includes the pressure to change grades (Tierney, 2015). Understanding such a context is essential.…”
Section: Reflections and Implicationsmentioning
confidence: 99%
“…Una de las responsabilidades que tiene el profesor en el aula es la de recopilar evidencias que sustenten en qué nivel se han logrado los aprendizajes esperados de un programa de estudios y asignar la calificación correspondiente a los alumnos. Este proceso de evaluación y calificación es relevante por las consecuencias que tiene ya sea de manera inmediata o cuando trasciende más allá de un ciclo escolar, porque de ello depende la continuación de estudios en grados superiores (Tierney, 2015); la calificación que se asienta en una boleta determina si el alumno es promovido de grado académico, si aparece en un cuadro de honor, si necesita clases de recuperación o si es aceptado en una institución superior (Guskey y Link, 2018); es decir, tiene un impacto en cuanto a las oportunidades futuras personales y educativas (Reeves, 2016). A pesar de la relevancia de las calificaciones para la educación y la investigación, como señala Chen y Bonner (2017), no se ha documentado de manera suficiente el proceso de toma de decisiones que explica cómo toma dicha decisión un docente y, es necesario conocer cómo están evaluando y calificando los profesores a sus alumnos para identificar en qué medida están considerando las pautas establecidas en los documentos oficiales como plan y programas de estudio (Gómez y Jakobsson, 2015), u otros documentos que orientan y regulan este proceso; o si sus prácticas están influenciadas por creencias personales sobre el aprendizaje, así como creencias y conocimientos sobre la calificación (Chen y Bonner, 2017).…”
Section: Introductionunclassified